2005
DOI: 10.1007/s10067-005-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

The symptomatic effects of intra-articular administration of hylan G-F 20 on osteoarthritis of the hip: clinical data of 6 months follow-up

Abstract: Hip osteoarthritis (OA) is usually managed with systemic treatments such as nonsteroidal anti-inflammatory drugs (NSAIDs) and/or symptomatic slow-acting drugs. Unfortunately, many patients either cannot tolerate NSAIDs or suffer serious, even fatal, NSAID-induced side effects, predominantly gastrointestinal ulceration and bleeding. Viscosupplementation, which aims to restore physiological and rheological features of the synovial fluid, is a well-accepted therapeutic option in knee OA patients, but limited data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Patients with mild morphological alterations, and with preserved articular space, are more responsive to treatment (22,48,50); the results are less encouraging in patients with severe OA (K-L IV) , only few studies report good therapeutic effects (20,22,48). In this regard, Bekerom has observed that VS may delay or avoid hip replacement in 45% of patients, so reducing costs and mortality (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with mild morphological alterations, and with preserved articular space, are more responsive to treatment (22,48,50); the results are less encouraging in patients with severe OA (K-L IV) , only few studies report good therapeutic effects (20,22,48). In this regard, Bekerom has observed that VS may delay or avoid hip replacement in 45% of patients, so reducing costs and mortality (22).…”
Section: Discussionmentioning
confidence: 99%
“…From the papers retrieved in the search the following data were extracted: sample size, inclusion / exclusion criteria, treatment procedures, evaluation methods, clinical results and follow-up duration. The case series, published by Migliore et al (16)(17)(18)(19)(20)(21) and Van den Bekerom et al (22,23), at different times, were considered cumulative. Methodological quality of included studies was assessed by assigning Levels of Evidence as previously defined by the Centre for Evidence Based Medicine (CEBM) (24).…”
Section: Methods Of Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In several previous studies, we reported on the short and medium-term clinical outcome obtained with different HA preparations when using this technique for treating patients with hip OA (30)(31).…”
mentioning
confidence: 99%
“…Patients with mild morphological alterations, and with preserved articular space, are more responsive to treatment (Brocq et al, 2002;Gaston et al, 2007;Van den Bekerom et al, 2006); the results are less encouraging in patients with severe osteoarthritis (Kellgreen -Lawrence IV), only few studies reporting a good therapeutic effects (Migliore et al, 2006b). Articular effusion usually is associated to a reduced therapeutic efficacy due to the "dilution effect" of the drug (Qvistgaard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%